A Study on English Affixation Found in Lyrics of Back to Friend by Sombr - Dhivia Purnama Arsiladeva; Otong Setiwan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Language is composed of various structural elements, and one of the most essential is morphology, the study of word formation and structure. This research explores the use of English affixation in the lyrics of Back to Friend by Sombr. The purpose of this study is to identify and analyze the affixes used in the song, focusing on both derivational and inflectional affixes. The analysis applies a descriptive qualitative method to examine how these affixes function within the lyrics, how they contribute to changes in grammatical categories, and how they affect meaning. Derivational affixes in the song often alter the word class, such as turning verbs into nouns or adjectives, while inflectional affixes serve to indicate grammatical aspects like tense, number, or aspect without changing the word class. The findings suggest that affixation plays an important role in the richness and expressiveness of the language used in song lyrics. This research also supports the use of popular songs as engaging material in linguistic and morphological studies.